THE INFLUENCE OF LEADERSHIP STYLE, WORK DISCIPLINE AND REWARDS ON ORGANIZATIONAL COMMITMENT - Tri Mulyani Kartini; Etty Zuliawaty Zed; Sinta Sundari Heriyanti; Pupung Purnamasari (SEAN Institute, 2023)
This study aims to examine the effect of leadership style, discipline, and reward on organizational commitment. The subject of this research is one of the companies engaged in manufacturing automotive wire in the Jababeka Cikarang area. This research is quantitative research and the sampling technique used is random sampling. Respondents who sampled this study were 80 employees. Technical data analysis using SPSS Statistic 25 software, the results showed partially that the leadership style variable had a positive and significant effect on organizational commitment. Discipline variables have no effect on organizational commitment. The reward variable has no effect on organizational commitment, therefore the influence of the existing leadership style and discipline and the provision of existing rewards will be able to support organizational commitment.